Observations and dynamical implications of active normal faulting in South Peru. Issue 1 (2nd April 2020) - Wimpenny, Sam; Benavente, Carlos; Copley, Alex; Garcia, Briant; Rosell, Lorena; O'Kane, Aisling; Aguirre, Enoch
SUMMARY: Orogenic plateaus can exist in a delicate balance in which the buoyancy forces due to gravity acting on the high topography and thick crust of the plateau interior are balanced by the compressional forces acting across their forelands. Any shortening or extension within a plateau can indicate a perturbation to this force balance. In this study, we present new observations of the kinematics, morphology and slip rates of active normal faults in the South Peruvian Altiplano obtained from field studies, high-resolution DEMs, Quaternary dating and remote sensing. We then investigate the implications of this faulting for the forces acting on the Andes. We find that the mountains are extending ∼NNE–SSW to ∼NE–SW along a normal fault system that cuts obliquely across the Altiplano plateau, which in many places reactivates Miocene-age reverse faults. Radiocarbon dating of offset late Quaternary moraines and alluvial fan surfaces indicates horizontal extension rates across the fault system of between 1 and 4 mm yr –1 —equivalent to an extensional strain rate in the range of 0.5–2 × 10 −8 1 yr –1 averaged across the plateau. We suggest the rate and pattern of extension implies there has been a change in the forces exerted between the foreland and the Andes mountains. A reduction in the average shear stresses on the sub-Andean foreland detachment of ≲4 MPa (20–25 per cent of the total force) can account for the rate of extension. These results show that, within a mountain belt, the pattern of faulting is sensitive to small spatial and temporal variations in the strength of faults along their margins.